Rapid Simultaneous Quantitative Determination of Ferric and Ferrous Ions in Geological Solution Sample with New Synthesized β-Diketone α-(2-Methoxy benzenthio) acetylacetone - H. ARBAB ZAVAR, MOHAMAD; EVAZMOGHADAM, SIMA; CHAMSAZ, MAHMUD; F. TAYARRI, SAYYED (Asian Journal of Chemistry, 2010)
A rapid and precise method for simultaneous measurement of ferrous and ferric ion concentrations in solution with new synthesized β-diketone (2-methoxy benzenthiol) acetyl acetone (hereafter 2MBTAA) is reported. The determination of both ferric and total iron concentration is carried out in the same solution at the same light wavelengths, which significantly reduces the error of the analytical procedure. The method is based on the colorimetric measurement of red coloured ferric β-diketone complex formed at low pH. After the addition of hydrogen peroxide, which leads to the oxidation of ferrous ion, the 2MBTAA forms a complex with all the iron ions in solution. The maximum wavelength of the complex was 464 nm. The relationship between iron concentration and the absorbance obeys Beer's law under the optimum conditions that were studied. The optimal ratio and volumes of the reagent used were also determined. The effect of the interference ions was studied, It was found that the colour complex was stable for a long time (at least 10 h).